Diffusion tensor imaging detects corticospinal tract involvement at multiple levels in amyotrophic lateral sclerosis. Issue 9 (21st August 2003) - Toosy, A T; Werring, D J; Orrell, R W; Howard, R S; King, M D; Barker, G J; Miller, D H; Thompson, A J
Abstract : Background: Histopathological studies of amyotrophic lateral sclerosis (ALS) are of end stage disease. Diffusion tensor imaging (DTI) provides the opportunity to investigate indirectly corticospinal tract pathology of ALS in vivo. Methods: DTI was used to study the water diffusion characteristics of the corticospinal tracts in 21 patients with ALS and 14 normal controls. The authors measured the fractional anisotropy (FA) and mean diffusivity (MD) along the pyramidal tracts from the internal capsules down to the pyramids. A mixed model regression analysis was used to compare FA and MD between the ALS and control groups. Results: FA showed a downward linear trend from the cerebral peduncles to the pyramids and was lower in the ALS group than controls at multiple levels of the corticospinal tract. At the internal capsules, FA was higher on the right. MD showed an upward trend, progressing caudally from the internal capsules to the pyramids. MD was higher at the level of the internal capsule in the ALS group, but caudally this difference was not maintained. No correlations were found between clinical markers of disability and water diffusion indices. Conclusions: These findings provide insights into the pathological processes of ALS. Differences in diffusion characteristics at different anatomical levels may relate to underlying tract architecture or the distribution of pathological damage in ALS. Further development may permit monitoring of progression and treatment of disease.